Acousto-optic diffraction of multicolour Ar-laser radiation in crystalline quartz. (October 2015) - Kotov, V.M.; Averin, S.V.; Voronko, A.I.; Kuznetsov, P.I.; Tikhomirov, S.A.; Shkerdin, G.N.; Bulyuk, A.N.
Abstract: We have studied acousto-optic Bragg diffraction of multicolour radiation, generated by an Ar laser in the blue-green region of the spectrum, on an acoustic wave propagating in crystalline quartz. It is shown that crystalline quartz significantly exceeds commonly used paratellurite in terms of phase matching of optical beams with a single acoustic wave. We have performed experiments on pulse modulation of Ar-laser radiation. It is shown that distortions introduced into optical pulses are substantially less when use is made of a quartz crystal rather than paratellurite.